Evolution of Rhetoric: An Analysis of Rhetorical Counsel to Rulers from the Classical to the Contemporary Era - Annajah, Shabrina Sakinah (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research aims to examine the rhetorical construction of leadership advice by focusing on the transition of language style from the classical era to the modern era. Because language reflects a person’s intellectual values and emotional intelligence, analyzing leadership speeches allows us to observe the distinctive internal qualities of a leader during their period of leadership. A leader does not lead merely with the sword, but with words—words that become a driving force in the lives of the people they govern. Through rhetorical analysis, we can understand how a leader builds the legitimacy of their leadership, manages crises with calming narratives, and mobilizes the masses toward specific goals. This comparative approach is crucial because the power of a leader’s oratory is not merely an instrument of communication, but an architecture of power that reflects mass psychology and the deconstruction of ideology in its time. Using the perspective of Balaghah, this qualitative research analyzes various speech texts to identify the linguistic devices employed by leaders in constructing authority. The findings of this study are expected to demonstrate the differences in linguistic characteristics, particularly the literary features that appear in speeches delivered by leaders across generations. These findings affirm that changes in rhetorical style are directly proportional to shifts in the paradigm of power within the social order of society.